The application of Interleukin-2 family cytokines in tumor immunotherapy research - Zhou, Yangyihua; Quan, Guiqi; Liu, Yujun; Shi, Ning; Wu, Yahui; Zhang, Ran; Gao, Xiang; Luo, Longlong (Frontiers in Immunology, 2023)
The Interleukin-2 Family contains six kinds of cytokines, namely IL-2, IL-15, IL-4, IL-7, IL-9, and IL-21, all of which share a common γ chain. Many cytokines of the IL-2 family have been reported to be a driving force in immune cells activation. Therefore, researchers have tried various methods to study the anti-tumor effect of cytokines for a long time. However, due to the short half-life, poor stability, easy to lead to inflammatory storms and narrow safety treatment window of cytokines, this field has been tepid. In recent years, with the rapid development of protein engineering technology, some engineered cytokines have a significant effect in tumor immunotherapy, showing an irresistible trend of development. In this review, we will discuss the current researches of the IL-2 family and mainly focus on the application and achievements of engineered cytokines in tumor immunotherapy.